Muscle Activity, and the Association between Core Strength, Core Endurance and Core Stability - Atle Hole Saeterbakken; Marius Steiro Fimland; Jonas Navarsete; Trine Kroken; Roland van den Tillaar (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2015)
Introduction: Core training is often divided into the training approaches core endurance-, core stability- and core strength training. The aim of the study was to compare the association between core strength, core endurance and core stability testing 52 healthy males and females.  Methods: The core strength and endurance tests were tested isometric in hip flexion, extension and lateral flexion. The time maintaining the positions in the core endurance tests, maximal force output in the core strength tests and total displacement in the core stability tests were examined with electromyography measurement of the core muscles in randomized order.  Results: There were no significant correlations between the variables core strength, core stability or core endurance (p = 0.102 - 0.965, r = 0.01 - 0.23), except for the endurance lateral flexion which correlated significantly with the core strength (extension and lateral flexion) and the core stability using the left leg (p = 0.001 - 0.048, r = 0.29 - 0.44). Generally, the muscle activity of the core muscle decreased from strength < endurance < stability tests, respectively. Conclusion: There were no systematic correlations between core endurance, core strength or core stability indicating that these capacities are largely independent from each other. Coaches, training instructors or physical therapists needs to address the core endurance, core strength and core stability as separate capacities and train them accordingly based on the aim of the training.